Have Developed Countries Escaped the Curse of Distance? - Boulhol, Hervé (OECD Economics Department Working Papers, 2008)
There is widespread evidence that a better access to markets contributes to raising income levels. However, no quantification of the impact of distance to markets has been made on the basis of a sample restricted to advanced - and therefore more homogeneous - countries. This paper applies the framework developed by Redding and Venables (2004) on a panel data covering 21 OECD countries over 1970-2004, and shows that, relative to the average OECD country, the cost of remoteness for countries such as Australia and New Zealand could be as high as 10% of GDP. Conversely, the benefit for centrally-located countries like Belgium and the Netherlands could be around 6-7%. Second, the paper explains why the key estimated parameter in the Redding-Venables model is biased upwards in cross-section samples that mix both developing and developed countries, because of the inability to adequately control for heterogeneity in technology levels across countries. The paper also provides a detailed discussion of the links between the ?death-of-distance? hypothesis, the evolution of transport costs and that of the elasticity of trade to distance